(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to the peculiarities of functioning of socially marked lexemes in the modern literary texts. Stylistic functions and expressive potential of social dialecticisms used in the modern Ukrainian prose texts are described.